2002
DOI: 10.1001/archpsyc.59.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Normal Sexual Dimorphisms on Sex Differences in Structural Brain Abnormalities in Schizophrenia Assessed by Magnetic Resonance Imaging

Abstract: Factors that produce normal sexual dimorphisms may be associated with modulating insults producing schizophrenia, particularly in the cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
143
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(157 citation statements)
references
References 90 publications
12
143
0
2
Order By: Relevance
“…Additionally, samples need to be comprised of both males and females, as there is clear evidence to suggest that the timing, course, and clinical features of schizophrenia are manifested quite differently in males and females, and this may be related to brain differences (Goldstein et al, 2002). It will also be important to evaluate a representative sample of normal controls across age, as white matter changes with age, and such changes may be quite different in pathological populations such as schizophrenia.…”
Section: Implications Conclusion and Future Directionsmentioning
confidence: 99%
“…Additionally, samples need to be comprised of both males and females, as there is clear evidence to suggest that the timing, course, and clinical features of schizophrenia are manifested quite differently in males and females, and this may be related to brain differences (Goldstein et al, 2002). It will also be important to evaluate a representative sample of normal controls across age, as white matter changes with age, and such changes may be quite different in pathological populations such as schizophrenia.…”
Section: Implications Conclusion and Future Directionsmentioning
confidence: 99%
“…Estrogens have also been shown to exert profound effects on brain differentiation during development, particularly during late gestation and the early postnatal period, and are important in normal maintenance of brain function during ageing [2][3][4][5]. In a well controlled magnetic resonance imaging study, Goldstein et al [3] showed that normal patterns of sexual brain dimorphism (brain regions found to be structurally different in normal men and women) are disrupted in schizophrenia and related psychoses, especially in the cortex.…”
Section: Basic Research Findingsmentioning
confidence: 99%
“…In a well controlled magnetic resonance imaging study, Goldstein et al [3] showed that normal patterns of sexual brain dimorphism (brain regions found to be structurally different in normal men and women) are disrupted in schizophrenia and related psychoses, especially in the cortex. Apart from later 'activational' effects of circulating hormones (e.g.…”
Section: Basic Research Findingsmentioning
confidence: 99%
“…Cognitive deficits rather than clinical diagnostic categories may better represent the underlying pathogenesis of schizophrenia (Gur et al, 2007). Several studies have focused on gender differences in the cognitive deficits of schizophrenia and showed gender differences in cognitive domains in both schizophrenia and healthy populations (Goldstein et al, 2002;Halari et al, 2006;Phillips and Silverman, 1997;Ragland et al, 1999;Wisner et al, 2011). Furthermore, gender differences in schizophrenia' cognitive deficits are evident in the prodromal symptoms, acute psychotic episodes, illness course, and clinical response to antipsychotic treatment (Grigoriadis and Seeman, 2002;Hughes et al, 2003;Rubin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%